Detection of interphylum transfers of the magnetosome gene cluster in magnetotactic bacteria - Uzun, Maria; Koziaeva, Veronika; Dziuba, Marina; Leão, Pedro; Krutkina, Maria; Grouzdev, Denis (Frontiers in Microbiology, 2022)
Magnetosome synthesis in magnetotactic bacteria (MTB) is regarded as a very ancient evolutionary process that dates back to deep-branching phyla. MTB belonging to one of such phyla, Nitrospirota, contain the classical genes for the magnetosome synthesis (e.g., mam, mms) and man genes, which were considered to be specific for this group. However, the recent discovery of man genes in MTB from the Thermodesulfobacteriota phylum has raised several questions about the inheritance of these genes in MTB. In this work, three new man genes containing MTB genomes affiliated with Nitrospirota and Thermodesulfobacteriota, were obtained. By applying reconciliation with these and the previously published MTB genomes, we demonstrate that the last common ancestor of all Nitrospirota was most likely not magnetotactic as assumed previously. Instead, our findings suggest that the genes for magnetosome synthesis were transmitted to the phylum Nitrospirota by horizontal gene transfer (HGT), which is the first case of the interphylum transfer of magnetosome genes detected to date. Furthermore, we provide evidence for the HGT of magnetosome genes from the Magnetobacteriaceae to the Dissulfurispiraceae family within Nitrospirota. Thus, our results imply a more significant role of HGT in the MTB evolution than deemed before and challenge the hypothesis of the ancient origin of magnetosome synthesis.